Muscle mass loss measured with portable ultrasound in hospitalized older adults: The ECOSARC study - Esther López Jiménez; Marta Neira Álvarez; Rocío Menéndez Colino; Marta Checa López; Concha Grau Jiménez; Patricia Pérez Rodríguez; Brian Vasquez Brolen; Estefanía Arias Muñana; Raquel Ramírez Martín; Cristina Alonso Bouzón; María Solange Amor Andrés; Cristina Bermejo Boixareu; et al. (Elsevier, 2024)
Objectives: The main objective was to analyze the evolution of muscle of the Quadriceps Rectus Femoris (QRF) between admission and discharge, in older adults hospitalized with an acute medical disease in Acute Geriatric Units (AGUs). Design: Prospective multicentric observational cohort study. Setting: Seven AGUs from University Hospitals in Spain. Participants: Hospitalized adults ≥ 70 years old, able to ambulate and without severe dementia. Measurements: Ultrasound measurements of QRF were acquired at 2/3 distal between anterior-superior iliac spine and patella in both legs by trained Geriatricians. Ultrasound Chison model ECO2 was used. QRF area, thickness, edema, echogenicity, and fasciculations were measured. Results: From the complete sample (n = 143), in 45 (31.5%) participants, ultrasound images were classified as non-valid by an expert radiologist. Mean age was 87.8 (SD 5.4). Mean hospital stay 7.6 days (SD 4.3). From those with valid images, 36 (49.3%), 2 (2.7%), and 35 (47.9%) presented a decrease, equal values, or an increase in QRF area from baseline to discharge, respectively, and 37 (50.0%), 2 (2.7%), and 35 (47.3%) presented a decrease, equal values, or an increase in QRF thickness, respectively. 26 (35.6%) presented a decrease in more than 0.2 cm2 of QRF area, and 23 (31.1%) a decrease in more than 0.1 cm of QRF thickness. Only 4 (5.4%) patients presented new edema, while 13 (17.6%) worsened echogenicity. Conclusion: One third of older adults develop significant muscle loss during a hospitalization for acute medical diseases. Trial registration number: NCT05113758